Adipocytes enhance expression of osteoclast adhesion‐related molecules through the CXCL12/CXCR4 signalling pathway. (21st November 2016) - Luo, Tingting; Liu, Hongrui; Feng, Wei; Liu, Di; Du, Juan; Sun, Jing; Wang, Wei; Han, Xiuchun; Guo, Jie; Amizuka, Norio; Li, Xianqi; Li, Minqi
Abstract: Objectives: The purpose of this study was to investigate effects of adipocytes on osteoclast adhesion‐related molecules. Materials and methods: ST2 cells, a cloned stromal cell line from mouse bone marrow, able to differentiate into adipocytes, were cultured in serum‐free α‐MEM which was then collected to be used as adipocyte‐conditioned medium (ADIPO CM). RAW264.7 cells were cultured in ADIPO CM in the presence of RANKL, and bone marrow‐derived macrophages were cultured in ADIPO CM in the presence of RANKL and macrophage‐colony stimulating factor to induce osteoclast differentiation. TRAP staining, resorption pit assay, qRT‐PCR and western blotting assays were performed. Results: ELISAs revealed that CXCL12 was abundant in ADIPO CM and CCK‐8 assay revealed no proliferation of RAW264.7 cells after exogenous CXCL12 treatment. ADIPO CM enhanced osteoclast formation and resorption, both by RAW264.7 cells and BMMs. In addition, exogenous CXCL12 efficiently potentiated formation of TRAP‐positive osteoclast and resorption by RAW264.7 cells. Western blotting and qRT‐PCR suggested that ADIPO CM or combined treatment with exogenous CXCL12 caused significant increase in expression of NFAT2, src and osteoclast adhesion‐related molecules, including β3 integrin, CD44 and osteopontin. However, these promotional effects were largely abrogated on treatment of AMD3100, a CXCR4 antagonist. Conclusions: Adipocytes promoted osteoclast differentiation, function and expression of adhesion‐related molecules through the CXCL12/CXCR4 signalling pathway.